Renewable Energy for Rural Development in Bangladesh - Fyza, Nashiyat; Sarkar, M. A. Rashid (Journal of the Institute of Engineering, 2020)
Energy is the key component to the development of a society. The demand for energy is increasing day by day. Around 16 percent of the global population does not have access to electricity. Around 64.96 % of the population of Bangladesh lives in the rural area. This large portion often suffers from substandard quality of electricity. But electricity production by conventional fossil fuel power plant gives rise to greenhouse gas emission including carbon dioxide, nitrogen oxides and sulfur dioxide. These gases cause global warming and climate change. This has a detrimental effect on every living thing on the planet. Such consequences put Bangladesh in a perilous position, as most of the land is less than 10 m above the sea-level. As lands become more prone to be inundated, this poses a threat to our agriculture, health, sanitation and causes scarcity of clean water. Initiatives must be taken to popularize low carbon climate resilient energy sectors for sustainable development. A brief study of different forms of renewable energy sources is dealt in this paper. In this study, the present scenario and future prospects of renewable energy in Bangladesh has been presented.